Somatic cells count and milk yield in high production Holstein cows - Coldebella, Arlei; Machado, Paulo Fernando; Demétrio, Clarice Garcia Borges; Júnior, Paulo Justiniano Ribeiro; Corassin, Carlos Humberto; Meyer, Paula Marques; Cassoli, Laerte Gagher (Pesquisa Agropecuaria Brasileira, 2003)
The goal of this paper was to evaluate if losses in milk yield due to increase in somatic cells count are proportional or independent of the level of production. A total of 7,756 observations, monthly collected from a single herd from September/2000 up to June/2002, were used. The lactation curve was modeled by the incomplete gamma function, considering the effects of lactation order, calving season, peripartum disorder incidence and body condition score at calving. Somatic cells count was added to the model as a multiplicative factor, representing relative losses, and as an additive factor, representing absolute losses. The best model was chosen based on the information criteria of Schwarz (BIC). The losses are absolute, becoming evident from 14,270 cells/mL, and they are 184 and 869 g/day for each increase of one unit in the natural logarithm scale, starting from that somatic cells count, for primiparous and multiparous cows, respectively.